Atlas of Spleen Pathology - O'Malley, Dennis P.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The spleen is an organ which has diverse functions including immunologic and hematologic. The Atlas of Spleen Pathology describes and selectively illustrates the normal and pathologic conditions that afflict the spleen. This extraordinary collection of high quality digital images will materially aid in continuing efforts to recognize, understand, and accurately interpret the gross and light microscopic findings in spleens.
Normal Morphologic and Immunohistochemical Findings and Hyperplasias -- Anatomy and Normal Histology -- Hyperplasias -- Normal Immunohistochemistry -- Congenital Malformations and Abnormalities of Spleen Location and Histology -- Accessory Spleen -- Intrapancreatic Spleen -- Polysplenia -- Splenosis -- Splenogonadal Fusion -- Other Findings -- Lymphoid Neoplasms -- Splenic Marginal Zone Lymphoma -- Chronic Lymphocytic Leukemia -- Lymphoplasmacytic Lymphoma -- Follicular Lymphoma -- Mantle Cell Lymphoma -- Plasma Cell Myeloma -- Hairy Cell Leukemia-Variant -- Splenic Diffuse Red Pulp Small B-Cell Lymphoma -- Prolymphocytic Leukemia -- Lymphoblastic Leukemia/Lymphoma -- Hepatosplenic T-cell Lymphoma -- T-cell Large Granular Lymphocytic Leukemia -- Other T-cell Lymphomas -- Diffuse Large B-cell Lymphomas -- Hodgkin Lymphoma -- Myeloid and Related Disorders -- Extramedullary Hematopoiesis -- Myeloid Sarcoma/Acute Myeloid Leukemia -- Myeloproliferative Neoplasms -- Myelodysplastic Syndrome and Myelodysplastic/Myeloproliferative Disorders -- Mastocytosis -- Histiocytic Sarcoma -- Nonhematopoietic Lesions Including Vascular -- Cysts -- Hamartoma -- Inflammatory Pseudotumor -- Follicular Dendritic Cell Tumor -- Other Stromal Tumors -- Splenic Artery Aneurysm -- Benign Vascular Lesions -- Littoral Cell Angioma -- Sclerosing Angiomatoid Nodular Transformation (SANT) -- Vascular Tumors of Indeterminate and Malignant Behavior -- Metastatic Tumors -- Reactive and Systemic Conditions -- Rupture and Trauma -- Infarction and Embolization -- Perisplenitis (Sugar-Coated Spleen) -- Congestive Splenomegaly -- Red Blood Cell Disorders -- Granulomas -- Langerhans Cell Histiocytosis -- Storage Diseases -- Castleman Disease -- Therapy Effects -- Other Disorders -- Hemophagocytic Syndrome -- Autoimmune Disorders -- Immunodeficiency (Inherited and Acquired) -- Infections -- Bacterial -- Mycobacteria -- Viruses -- Fungi -- Parasites and Protozoa.
Keywords: Pathology; Pathology